Smoothing Control of Wind Farm Output Fluctuations by Fuzzy Logic Controlled SMES - Md. Rafiqul Islam Sheikh; Tamura Junji (Institute of Advanced Engineering and Science, 2011)
Due to random variations of wind speed, the output power and terminal voltage of a fixed speed wind generator fluctuate continuously. These irregularities in power output are affecting both the power quality and reliability. It is reported that STATCOM/SMES (Superconducting Magnetic Energy Storage) system can significantly decrease voltage and output power fluctuations of grid connected fixed speed wind generator. But the main problem in wind generator output power smoothing is the choice of the reference output power, because it corresponds to energy storage capacity. The storage capacity of SMES that is sufficient for the smoothing control but as small as possible is very important, considering cost effectiveness. In this paper, a fuzzy logic controlled STATCOM/SMES system is proposed, in which both SMA (Simple Moving Average) and EMA (Exponential Moving Average) are used to generate output power reference. Real wind speed data are used in the simulation analyses, whichvalidate the effectiveness of the proposed control strategy. Simulation results clearly show that the proposed STATCOM/SMES system can smooth well the wind generator output power and also maintain the terminal voltage at rated level in both cases when SMA or EMA is used to generate output reference power. Finally, it is shown that reference output power generated by EMA provides better performance with reduced SMES storage capacity than that of output power generated by SMA.Keywords: Minimization of fluctuations, fixed speed wind generator, STATCOM/SMES, simple moving average (SMA) and exponential moving average (EMA), and wind farm (WF).DOI:http://dx.doi.org/10.11591/ijece.v1i2.181